E-Module with Wordwall for Junior High Cognitive Outcomes: Modul Elektronik dengan Wordwall untuk Hasil Kognitif Siswa SMP - Nafisah; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2025)
General background: Interactive digital media can improve student engagement in science learning. Specific background: At SMP Muhammadiyah 1 Taman, conventional textbooks dominated instruction while student engagement remained low. Knowledge gap: Limited evidence exists on combining e-modules with embedded Wordwall games for junior high temperature, heat, and expansion topics. Aims: This quasi-experimental study examined cognitive learning outcomes after implementing an e-module containing Wordwall activities compared with textbook instruction. Results: A saturated sample of 56 seventh-grade students (28 experimental, 28 control) showed higher N-Gain in the experimental group (0.56 vs 0.23) and a statistically significant difference (t test, p < 0.001). Novelty: The study integrates interactive Wordwall games within an e-module, linking multimedia elements to cognitive domain gains. Implications: Findings suggest that blended e-module and game-based activities offer a practical, engaging alternative for junior high science instruction, with considerations for internet access and offline adaptation.Highlights: Interactive e-module combined with Wordwall games. Significant N-Gain improvement in experimental group. Strong gains in higher-order cognitive levels (C5–C6). Keywords: E-Module, Wordwall, N-Gain, Cognitive Learning, Junior High